Co-digestão anaeróbia de resíduos vegetais e águas residuárias de suinocultura em reatores horizontais de leito fixo e alta taxa - Mazareli, Raissa Cristina da Silva [UNESP] (2014)
Four horizontal fixed bed and high rate reactors were used to evaluate the removal of organic matter, coliforms and nutrients and also the production of methane in anaerobic co-digestion process using as a substrate different concentrations of vegetable waste (tomato and banana) and swine wastewater. Physical and chemical analyzes were performed in the influent and effluent in order to verify system stability. The results showed buffering efficiency in the process, maintaining the pH near 7,0. The first reactor (R1) occurred the maximum volumetric production of methane with average values of 1,08 L CH4 (Ld-1) with OLR of 11 g DQO (Ld)-1. The biggest specific production of methane occurred at the beginning of the test 4 with 0,25 L CH4 g total COD removed in the R1, equivalent to 88% of total COD removed was converted to methane. The specific production of methane g dissolved COD was higher with application of OLR of 5,5 g COD (Ld) -1 the first reactor. The CH4 decreased when there was vegetable waste increase in inffluent. The system (R1+R2+R3+R4) improved the quality of the inffluent with removal of 99,99% of total and fecal coliforms as well as maximum removal of 95% of total COD, 86% of dissolved COD, 97% of TSS and 98% of VSS. The system also occurred accentuated removal of macro and micronutrients (86, 75, 95, 99, 96, 63 and 83% of total P, Mg, Zn, Cu, Mn, Fe and total nitrogen respectively), and sludge production with relationship SV/ST for agricultural use. Reactors profile analysis demonstrated removal of the organic matter and production of biogas would need only three reactors ...